CO2 gas-adsorption calorimetry applied to the study of chemically activated carbons - Soares Maia, Debora Aline (2018)
In this work, the microporous structure of a series of H3PO4 chemically activated carbons from peach stones with increased activation degree were investigated. CO2 Adsorption equilibrium isotherms and differential enthalpy curves were simultaneously measured at 300 K using a Tian-Calvet microcalorimeter coupled to an adsorption manometric setup. Temperature programmed decomposition experiments were used to assess density of oxygen functional groups and determine the impact of surface chemistry on CO2 adsorption capacity. Computer based theoretical calculations were also performed to attempt to predict the adsorption enthalpy profiles. The most activated sample (Xp = 0.90) has an average adsorption enthalpy which is approximately 8 kJ/mol lower than that of the non-activated samples carbonized under the same conditions. The combination of techniques enabled a better understanding of the pore filling regimes with increasing coverage, since the use of CO2 as a probe gas allows accessing small pores, which otherwise would not be identified from N2 isotherms at 77 K. The oxygen content on the carbon surface decreased almost 80% with the increasing degree of activation and did not influence in the CO2 adsorption. Besides providing information about carbon chemistry, CO2 adsorption calorimetry can also be successfully applied to the screening of carbons intended for CO2 capture.